An introduction to the law of international criminal tribunals : a comparative study - Knoops, Geert-Jan Alexander, 1960- (International criminal law series (Leiden, Netherlands), 2014)
In An Introduction to the Law of International Criminal Tribunals Geert-Jan Alexander Knoops offers an overview of the basic topics in international criminal law (ICL). It discusses main characteristics of International Criminal Tribunals (ICTs), as well as definitions of international crimes. The book will delve into issues of jurisdiction and complementarity, liability principles and specialized defences. Other topics are: due process rights, evidence, trials in absentia and State cooperation. A new chapter is devoted to the geopolitical effects of international criminal prosecutions. The second revised edition includes a chapter on the "new" crime of aggression and is updated with the most recent developments in ICL. The book is essential to everyone becoming familiar with the basic topics and challenges within ICL.--